Butanol production from sweet sorghum bagasse with high solids content: Part I—comparison of liquid hot water pretreatment with dilute sulfuric acid. (27th July 2018) - Qureshi, Nasib; Saha, Badal C.; Klasson, K. Thomas; Liu, Siqing
Abstract : In these studies, we pretreated sweet sorghum bagasse (SSB) using liquid hot water (LHW) or dilute H2 SO4 (2 g L −1 ) at 190°C for zero min (as soon as temperature reached 190°C, cooling was started) to reduce generation of sugar degradation fermentation inhibiting products such as furfural and hydroxymethyl furfural (HMF). The solids loading were 250–300 g L −1 . This was followed by enzymatic hydrolysis. After hydrolysis, 89.0 g L −1 sugars, 7.60 g L −1 acetic acid, 0.33 g L −1 furfural, and 0.07 g L −1 HMF were released. This pretreatment and hydrolysis resulted in the release of 57.9% sugars. This was followed by second hydrolysis of the fibrous biomass which resulted in the release of 43.64 g L −1 additional sugars, 2.40 g L −1 acetic acid, zero g L −1 furfural, and zero g L −1 HMF. In both the hydrolyzates, 86.3% sugars present in SSB were released. Fermentation of the hydrolyzate I resulted in poor acetone‐butanol‐ethanol (ABE) fermentation. However, fermentation of the hydrolyzate II was successful and produced 13.43 g L −1 ABE of which butanol was the main product. Use of 2 g L −1 H2 SO4 as a pretreatment medium followed by enzymatic hydrolysis resulted in the release of 100.6–93.8% (w/w) sugars from 250 to 300 g L −1 SSB, respectively. LHW or dilute H2 SO4 were used to economize production of cellulosic sugars from SSB. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:960–966, 2018